Helping Solve the “Other” Taxonomic Impediment: Completing the Eight Steps to Total Enlightenment and Taxonomic Nirvana - Evenhuis, Neal L. (Zootaxa, 2007)
Simply put: despite over ten years of recognizing the problem and giving it a catchy phrase, we still lack the taxonomic expertise to effectively describe the remaining biodiversity on earth. How can we enjoy and protect something if we don’t know it is out there to enjoy and protect?